Data encryption in e-counselling system (DEECS) - Athirah Fayyadhah, Othman (2009)
Communication has changed dramatically in recent years and many people now use the internet as the central role in their contact with friends, family and work colleagues. This social side to the web has been very successful and already been used at modern country like America. It is almost the expected way to do business. Previously, all the information of student was recorded manually by counsellor on paper. So, it have no guarantee of the security that the information would not be stolen or read by someone else and no security mechanism to ensure such data be read or handled in secure manner. The purpose of this project is to apply symmetric key (secret key) for encrypted memo in order to secure counselling session. This technique overcomes the problem of security in counseling session to ensure such data be read or handled in secure manner. Therefore, confidentiality can be achieve in this project.